Kontribusi Muhammad Sa'id Ramadhan Al-Buthi Dalam Pemikiran Hukum Publik Islam - Mufid, Moh. (Al-Jinayah: Jurnal Hukum Pidana Islam, 2018)
Abstract: This paper discusses about al-Buthi's thoughts in the field of Islamic criminal law. Al-Buthi concludes that critics of Islamic criminal law are too simplistic and superficial. Because Islamic criminal law actually accommodates the interests of victims of criminal acts and also aims to create a conducive and productive society. In this context, al-Buthi asserted that the implementation of punishment in Islamic criminal conduct is procedurally through rigorous verification. Apart from that, it also pays attention to other aspects, such as the conditions and situations in which the crime occurred. Philosophically, punishment in Islam must contain two elements: ibrah and zajr. Al-Buthi assessed that punishments in Islamic crimes are relevant to the purpose of maqasid sharia to create a safe and conducive society. Keywords: Contributions, Muhammad Sa'id Ramadhan al-Buthi, Thought of Islamic Criminal Law.                                  Abstrak: Tulisan ini membahas pemikiran al-Bûthi di bidang hukum pidana Islam. Al-Bûthi menyatakan bahwa para pengkritik hukum pidana Islam terlalu simplifikatif dan dangkal, padahal hukum pidana Islam sejatinya mengakomodasi kepentingan korban tindak kriminalitas dan juga bertujuan menciptakan masyarakat yang kondusif dan produktif. Pada konteks ini, al-Bûthi menegaskan bahwa pelaksanaan hukuman dalam pidana Islam dilakukan secara prosedural melalui pembuktian yang ketat. Selain itu, hukuman dalam pidana Islam juga memperhatikan aspek lain, misalnya kondisi dan situasi dimana tindak pidana tersebut terjadi. Secara filosofis, hukuman dalam Islam harus mengandung dua unsur: ibrah dan zajr. Al-Bûthi menilai hukuman dalam pidana Islam relevan dengan tujuan maqasid syariah untuk menciptakan masyarakat yang aman dan kondusif. Kata Kunci: Kontribusi, Muhammad Sa’id Ramadhan al-Bûthi, Pemikiran Hukum Pidana Islam.